Jewish Odesa : negotiating identities and traditions in contemporary Ukraine - Sapritsky-Nahum, Marina (Modern Jewish experience (Bloomington, Ind.), 2024)
"Jewish Odesa: Negotiating Identities and Traditions in Contemporary Ukraine explores the rich Jewish history in Ukraine's port city of Odesa. Long considered both a uniquely cosmopolitan and Jewish place, Odesa's Jewish character has shifted since the Soviet Union collapsed and Ukraine gained its independence. Drawing on extensive field research, Marina Sapritsky-Nahum, examines how the role of Russian language and culture, memories of the Soviet political project, and Odesan's place in a Ukrainian national project have all been questioned in recent years. Jewish Odesa reveals how a city once famous for its progressive Jewish traditions has become dominated by Orthodox Judaism and framed by the agendas of international Jewish organizations embedded in a religiosity that is foreign to the city. Russia's war in Ukraine has forced Jewish identities with ties to Odesa to change still further"--